Simulasi Jam Alarm Otomatis Untuk Mengetahui Waktu Aktivitas Santri di Pondok Pesantren: Praktik Jam Alarm Otomatis Menggunakan Wokwi - Akhlis Munazilin; Roy Hanul Wafa; Muhammad Faril Hakim; Muhammad Sahril Ramadhani (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Time discipline is an important factor for daily life, especially in Islamic boarding schools. Various activities carried out by students such as congregational prayer, reciting the Koran, studying, and resting at night are carried out on a schedule/time determined by the boarding school administrators. However, the notification process to the students is done manually so that many students are careless in the matter of keeping time, so that it can cause delays and inefficiencies regarding the time determined by the Islamic boarding school. Perhaps with this learning, the aim is to design and implement an automatic alarm clock based on Ardino Uno using the Wokwi simulator as a medium for development and testing on students. The system utilizing this module is very valuable for students who are obedient in participating in activities both from congregational prayer activities and mandatory activities of the students. This system utilizes all aspects of the DS1307 real time clock (RTC) module to obtain time information conducively, an I2C LCD as a display medium and a buzzer as a sound notification device. This practical learning method was used to analyze requirements, design the system, implement simulations, and test its functionality. The results of this practical learning demonstrated that the system is capable of displaying the time in real time and providing automatic alarms according to the pre-programmed schedule of mandatory Islamic boarding school activities.